Influence Law of Interbedded Strata and Their Collapse on the Mining of Extremely Thick Coal Seam under Goaf. (11th February 2019) - Ji, Chunxu; Yang, Yongkang; Guo, Xingyun; Kang, Tianhe; Guo, Zefeng
Abstract : Interbedded strata and their collapse are vital to mining pressure control for extremely thick coal seam under goaf. To ensure the stability of the support and to avoid roof collapse, some traditional underground pressure theoretical models had been widely used in the control of surrounding rock and the selection of support. However, one of the challenges for extremely thick coal seam under goaf is that the abnormal disasters, such as support crushing and water inrush that were occurring frequently. To solve this problem, the movement characteristics of overburden rocks during the mining of extremely thick coal seam under the conditions of the interlayer thickness of 5 m and 40 m were studied by using the similar simulation experiments, while the numerical simulation experiments were carried out for the interval between coal seams of 15 m and 60 m, respectively. Finally, the structure and mechanical transfer mechanism of overburden in stope under different thickness interbedded strata were analyzed dynamically, and the condition of full-thickness connection between upper goaf and lower goaf and corresponding judgment criteria are obtained. These results can guide future research on the mechanical of extremely thick coal seam under goaf, which can provide a theoretical basis and engineering reference for similar projects.